Cognitive Behavioral Therapy for Chronic Pain - Afrina, Riska; Karimah, Azimatul (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Pain is a complex stressor that has a major influence on several aspects of a person's physical, psychological, work and financial functions, especially in the form of chronic pain. The approach to chronic pain medically can sometimes not solve the problem as a whole, so that in its management psychological approaches such as cognitive and behavioral therapy (CBT) are needed.Methods: We searched PubMed, Science Direct, and Google Scholar for search articles in English terms